Pengaruh Penggunaan Aplikasi Madzas (Pendeteksi Bahasa Bayi) Terhadap Ketepatan Pemberian Penanganan pada Bayi Bagi Ibu Primipara di Wilayah Desa Binaan PKM Bangetayu Semarang - Maria Friska Kristiany; Agnes Isti Harjati; Mudy Oktiningrum (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Dunstan Baby Language (DBL) identifies five distinct infant vocalizations (“neh”, “owh”, “eh”, “eairh”, “heh”), each associated with a specific need. An Android application, Madzas, translates these vocalizations, aiding caregiver understanding. This study, conducted within a Community Service (PKM) program focused on village community development, investigated the impact of Madzas on the accuracy of care provided to infants by first-time mothers in the Bangetayu Public Health Centre Service Area. This true experimental study, employing a case-control approach, was conducted in the Bangetayu Public Health Centre Service Area, Semarang city. The study population consisted of primiparous mothers with infants aged 1-3 months, with a sample size of 46 mothers selected using purposive sampling. The participants were divided into case and control groups. The data were analysed using the Mann-Whitney U test, revealing a statistically significant effect (p < 0.05) of using the Madsaz application on the accuracy of care provided by the mothers. The findings indicated a high accuracy rate (z = 2.094) in treatment decisions among the mothers who used the application, supporting the hypothesis that the application positively influences caregiving accuracy in the studied population.